2014
DOI: 10.1186/2055-0391-56-11
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Conjugated Linoleic Acid (CLA) increases milk yield without losing body weight in lactating sows

Abstract: This study was conducted to evaluate the effects of dietary conjugated linoleic acid (CLA) on the performance of lactating sows and piglets as well as the immunity of piglets suckling from sows fed CLA. Eighteen multiparous Duroc sows with an average body weight (BW) of 232.0 ± 6.38 kg were randomly selected and assigned to two dietary treatments (n = 9 for each treatment), control (no CLA addition) and 1% CLA supplementation. For the control diet, CLA was replaced with soybean oil. Experimental diets were fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 49 publications
(76 reference statements)
4
17
1
2
Order By: Relevance
“…In the present study, the reduction in milk fat concentration was approximately 20 %, which is in accordance with the results of other studies in sows (approximately 14-36 % (33,34) ). Variation in responses may be due to the level and time of supplementation, the major isomer used, and the genotype and physiological state of the individual animals (11) . A negative effect of CLA on milk protein content was observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the reduction in milk fat concentration was approximately 20 %, which is in accordance with the results of other studies in sows (approximately 14-36 % (33,34) ). Variation in responses may be due to the level and time of supplementation, the major isomer used, and the genotype and physiological state of the individual animals (11) . A negative effect of CLA on milk protein content was observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty multiparous sows from a commercial genotype (Aurora Genetics) in their 1st-5th parities and weighing (BW) 200 (SE 10) kg were randomly assigned to one of the following treatments: (1) control, without CLA added to the diet; or (2) 1 % CLA (containing 4•1 % palmitic acid, 3•6 % stearic acid, 27•4 % oleic acid, 1•2 % linoleic acid, 29•8 % cis-9, trans-11-CLA, 29•9 % trans-10, cis-12-CLA and 3•0 % other fatty acids) mixed into the diet. The amount of CLA mixed into the feed was based on the procedure outlined in Lee et al (11) .…”
Section: Animals Design and Treatmentsmentioning
confidence: 99%
“…Tal vez por esta razón, ambos grupos analizados presentaron el mismo comportamiento productivo (kg de leche d -1 ). Lee et al (2014;5) observaron una producción promedio de 8.5 kg de leche cerda -1 en lactancia de 21 días. Resultado mayor al encontrado en esta investigación: 7.2 ± 2.2 y 7.4 ± 2.7 kg de leche, para el GT y GE, respectivamente (Tabla 4).…”
Section: Discussionunclassified
“…Esta diferencia entre lo reportado por Lee et al (2014;5) y los resultados de la presente investigación, pudo deberse principalmente a aspectos genéticos, ello sin descartar los aspectos ambientales (Farmer y Quesnel, 2009, 56).…”
Section: Discussionunclassified
“…Two papers reviewed in the previous opinion provided indirect evidence that CLA might improve reproductive performance in sows. Cordero et al (2011) reported a study with 17 lactating sows receiving no CLA and 17 receiving dietary CLA (10 g CLA/kg diet), while Lee et al (2014) described a similar trial with 9 sows per treatment. Both papers reported a statistically significant decrease in loss of backfat in the CLA group during lactation.…”
Section: Efficacy For Sows For Reproductionmentioning
confidence: 99%